Pemanfaatan Batu Gunung Posi’padang Balla Kabupaten Mamasa Sebagai Campuran AC-BC - Newman Archimedes Salmon; Alpius; Charles Kamba (Paulus Civil Engineering Journal, 2020)
This research is intended to Utilize Posi Mountain Stone as a Mixed Material of AC-BC. The methodology in this research is to conduct a series of testing the characteristics of coarse, fine aggregate, and filler then design the composition of the Laston AC-BC mixture and Marshall test to obtain the mixture characteristics and Marshall immersion test to obtain an immersion index (IP) / residual strength index (IKS) / optimum durability of asphalt mixtures.The results of research conducted at the Road and Asphalt Laboratory of the Faculty of Engineering, Department of Civil Engineering, Christian University of Indonesia, Makassar Makassar, showed that the characteristics of pavement materials in the form of Serang Tengnge mountain rocks, Kapalapitu District, meet specifications as road pavement coating materials. Through the Marshall Test obtained the characteristics of the mixture Laston AC-WC with asphalt content of 5.0%, 6, 0%, 6, 50%, 7.00%, 7.50%. The Marshall immersion test results of the laston AC-WC mixture with an optimum asphalt content of 7.0% obtained an Immersion Index (IP) / Residual Strength Index (IKS) / Durability of 95.74%, which fulfill 90% compliance and meet 2018 Highways Quality Specifications.